Laser ablation damage tolerance test method and device for ceramic matrix composite material
Through laser ablation test and finite element simulation method, the problem of damage tolerance evaluation of ceramic matrix composites under laser ablation damage was solved, and the accurate damage tolerance prediction and ablation resistance evaluation of ceramic matrix composites were achieved. The scope of injury type research has been expanded and the testing cost has been saved.
Patent Information
- Application Number
- CN202411813946.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art is difficult to effectively evaluate the damage tolerance of ceramic matrix composites under laser ablation damage, especially in non-contact damage scenarios, and its residual performance cannot be accurately predicted.
A laser ablation damage tolerance test method for ceramic matrix composites is designed, including laser ablation test using pourable flat-mouth clamping samples, high-energy laser components, high-speed cameras and infrared cameras, and adjustments through finite element simulation parameters to form an accurate simulation method for ablation resistance.
A scientific evaluation of the damage tolerance of laser ablation of ceramic matrix composite materials has been achieved, the scope of damage type research is expanded, accurate prediction ability is provided, test costs are saved, and high-temperature damage tolerance can be simulated under various operating conditions. value.
Smart Images

Figure CN119290728A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of laser ablation testing, and in particular to a laser ablation damage tolerance testing method and device for ceramic-based composite materials. Background Art
[0002] In recent years, the aerospace field has become increasingly demanding on the service performance of materials. In the aerospace field, the leading edge temperature of the wing of a hypersonic aircraft is at 2000℃ or even 3000℃, and it needs to be used as a load-bearing structure, which places high demands on the mechanical-thermal-chemical properties of the material. In the aviation field, the service temperature of the combustion chamber of a new engine has reached 2000℃. Ceramic-based composites have excellent properties such as lightweight, high specific modulus and high temperature resistance, and have been widely used in hot end components in the aerospace field.
[0003] In the field of aircraft structural design, when a pre-damaged structure cannot be repaired in time and needs to continue to serve, maintenance personnel need to reasonably evaluate the remaining performance of the damaged parts. According to existing design standards, structural damage tolerance is mainly aimed at foreign object impact scenarios, which is often referred to as contact damage. However, with the emergence and application of high-energy laser weapons, high-energy lasers can directly ablate aircraft structures and cause damage, which has expanded the type of structural damage from contact impact damage to non-contact laser ablation damage.
[0004] At present, fuselage and wing parts are made of resin-based composite materials, while the core high-temperature resistant parts of the engine are ceramic-based composite materials. When subjected to laser ablation impact, they all face problems related to damage tolerance. Based on the above needs, it is necessary to develop a damage tolerance test platform and test method for laser ablation aircraft structures and materials. The present invention is specifically designed for the scientific problem of damage tolerance of high-temperature resistant ceramic-based composite materials.
[0005] Therefore, it is necessary to design a laser ablation damage tolerance test method for ceramic matrix composites. Summary of the invention
[0006] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art and to provide a laser ablation damage tolerance test method and device for ceramic matrix composite materials.
[0007] To achieve the above object, the technical solution adopted by the present invention is as follows: A laser ablation damage tolerance test method for ceramic matrix composite materials, comprising the following steps: Step 1, preparing a test device: the test device comprises a tiltable flat-nose pliers, a ceramic matrix composite material sample, a high-energy laser assembly, a high-speed camera, and a plurality of infrared cameras; the ceramic matrix composite material sample is clamped by the tiltable flat-nose pliers, a high-energy laser assembly is used to emit a high-energy laser to the ceramic matrix composite material sample, an image of the test process is captured by the high-speed camera, and a thermal distribution cloud map of the ceramic matrix composite material sample is captured by the infrared camera; Step 2, performing a laser impact test: the tiltable flat-nose pliers clamp and fix the ceramic matrix composite material sample, the high-energy laser assembly aims at the middle position of the front side of the ceramic matrix composite material sample to emit a high-energy laser, the high-speed camera photographs the coating falling off and fiber ablation on the surface of the ceramic matrix composite material sample, and the infrared camera photographs the thermal distribution cloud map of the front, back and side of the ceramic matrix composite material sample; Step 3: Analyze the test results: draw the "ablation depth-optical power" and "ablation radius-optical power" test curves and obtain the corresponding optical power values at the inflection points of the curves respectively. and The residual tensile properties of the ceramic matrix composite material sample were measured using an electronic universal testing machine, the damage tolerance was characterized by the residual tensile strength, a "residual tensile strength-optical power" curve was drawn, and the optical power value corresponding to the inflection point of the curve was obtained. ; Step 4, perform finite element simulation on the laser impact test: establish a model of the ceramic matrix composite material in COMSOL software, set the parameters of the ceramic matrix composite material and the laser ablation related parameters and formulas to simulate the process of laser ablation of the ceramic matrix composite material; compare the ablation radius and ablation depth of the ceramic matrix composite material under different ablation times and light powers, draw the "ablation depth-light power" and "ablation radius-light power" simulation curves and obtain the light power values corresponding to the inflection points of the curves respectively. and ; Step 5: Comparative test results , and the simulated , By adjusting the simulation parameters in the COMSOL software, the experimental results are consistent with the simulation results, forming a simulation method that can accurately predict the anti-ablation performance of ceramic matrix composites.
[0008] Furthermore, the high-energy laser assembly includes a high-energy laser, a freely rotating gimbal, a low-energy laser aimer, and a water-cooled radiator. The high-energy laser is used to emit a high-energy laser, the freely rotating gimbal is used to drive the high-energy laser to rotate to adjust the emission direction, the low-energy laser aimer is used to emit an aiming laser, and the water-cooled radiator is used to dissipate heat from the high-energy laser.
[0009] Furthermore, three infrared cameras are provided, and the three infrared cameras respectively shoot toward the front side, the back side and the side of the ceramic-based composite material sample.
[0010] Furthermore, in step 3, the microscopic morphology of the ablated region of the ceramic matrix composite material sample is observed under an optical microscope, and the degree of ablation of different components under different working conditions is compared.
[0011] Further, in step 3, and In The one with the closer value; if and If the ablation depth is closer, the ablation depth is used as the parameter to characterize the tensile damage tolerance of ceramic matrix composites; and To be closer, the ablation radius is used as a characterization parameter for the tensile damage tolerance of ceramic matrix composites.
[0012] Furthermore, in step 4, the laser ablation related formula specifically includes: Assuming that the distribution of charged particles is isotropic and considering only the spatial variation in the thickness direction of the material, we take the thickness direction as x coordinates, the microscopic state of electrons and ions can be expressed by the distribution function , Description, satisfying the following Vlasov equations: ; ; in, is the electron charge, is the electron mass, is the self-consistent electric field strength, is the ion mass, is the ionic charge, is the ionic charge number, is the average number density of free electrons, is the average ion number density, is the speed of light, , are the source terms for producing free electrons and ions respectively; It's time. It’s speed; For femtosecond lasers, free electrons and ions are generated by two mechanisms: multiphoton ionization and avalanche ionization, namely: ; Among them, the subscript or ; is the multiphoton ionization rate, calculated by the Keldysh formula; ; in, is the laser power; , are complete elliptic integrals of the first and second kind, respectively; is the Keldysh parameter of the solid, expressed as: ; Parameters and Parameters according to The parameters are calculated: ; ; in, is the reduced Planck constant, is the band gap energy of the material, is the reduced mass of electrons and holes, is the hole mass; ; in, yes The integer part of: ; is the Dawson integral: ; is the photon ionization distribution, which is an arbitrary normalized function; ; is the avalanche ionization rate: ; in, is the avalanche ionization coefficient, It's electric current.
[0013] The present invention also provides a laser ablation damage tolerance test device for ceramic-based composite materials, comprising a tiltable flat-nose pliers, a ceramic-based composite material sample, a high-energy laser assembly, a high-speed camera, and several infrared cameras. The tiltable flat-nose pliers clamp the ceramic-based composite material sample, the high-energy laser assembly is arranged in front of the ceramic-based composite material sample to emit high-energy laser toward the front of the ceramic-based composite material sample, the high-speed camera is arranged in front of the ceramic-based composite material sample to shoot toward the front of the ceramic-based composite material sample, and the infrared camera shoots toward the ceramic-based composite material sample.
[0014] Furthermore, the high-energy laser assembly includes a high-energy laser, a free-rotating gimbal, a low-energy laser sight, and a water-cooled radiator. The high-energy laser and the low-energy laser sight are arranged on the free-rotating gimbal. The high-energy laser is used to emit a high-energy laser. The free-rotating gimbal is used to drive the high-energy laser to rotate to adjust the emission direction. The low-energy laser sight is used to emit an aiming laser, and the aiming laser is parallel to and close to the high-energy laser. The water-cooled radiator is arranged on the high-energy laser to dissipate heat from the high-energy laser.
[0015] Furthermore, three infrared cameras are provided, and the three infrared cameras are respectively arranged in front of, behind and on one side of the ceramic-based composite material sample.
[0016] It can be seen from the above description of the present invention that, compared with the prior art, the laser ablation damage tolerance test method of the ceramic matrix composite material of the present invention includes at least one of the following beneficial effects: 1. The present invention directly clamps the ceramic matrix composite material sample by tiltable flat-nose pliers, and can easily clamp and replace the sample; the present invention aims the ceramic matrix composite material sample with a low-energy laser aimer in advance, and can achieve high-energy laser ablation at a precise position; 2. The present invention can apply a temperature gradient. By applying high-energy laser ablation on one side of the ceramic-based composite material sample, single-sided heating can be achieved, which solves the problem that the two sides of the sample in the traditional heating furnace are heated more evenly, but it is difficult to generate a temperature gradient; 3. The present invention proposes the concept of laser ablation damage tolerance of ceramic matrix composites, which expands the research scope of damage tolerance from contact damage to non-contact damage; 4. The present invention proposes a finite element simulation method for the laser ablation damage tolerance of ceramic-based composite materials, which can simulate and predict the high-temperature damage tolerance values under various working conditions, saving test costs. The parameters of the finite element simulation are adjusted based on actual test results to ensure the accuracy of the simulation. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 A flowchart of the steps of a laser ablation damage tolerance test method for a ceramic matrix composite material in a preferred embodiment of the present invention; Figure 2 It is a structural schematic diagram of a laser ablation damage tolerance test device for ceramic-based composite materials in a preferred embodiment of the present invention; Explanation of the numbers in the figure: 1 tiltable flat-nose pliers, 2 ceramic-based composite material sample, 3 high-speed camera, 4 infrared camera, 5 high-energy laser, 6 free-rotating pan / tilt head, 7 low-energy laser aimer, 8 water-cooled radiator. DETAILED DESCRIPTION
[0020] The technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0021] In the description of the present invention, it should be noted that the terms "upper", "lower", "inner", "outer", "top / bottom" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific position, be constructed and operated in a specific position, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.
[0022] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "provided with", "mounted / connected", "connected", etc. should be understood in a broad sense. For example, "connected" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0023] Reference Figure 1 As shown, a preferred embodiment of the present invention is a laser ablation damage tolerance test method for ceramic matrix composite materials, comprising the following steps: Step 1, preparing a test device: the test device comprises a tiltable flat-nose pliers 1, a ceramic matrix composite material sample 2, a high-energy laser assembly, a high-speed camera 3, and a plurality of infrared cameras 4; the ceramic matrix composite material sample 2 is clamped by the tiltable flat-nose pliers 1, a high-energy laser assembly is used to emit a high-energy laser to the ceramic matrix composite material sample 2, an image of the test process is captured by the high-speed camera 3, and a thermal distribution cloud map of the ceramic matrix composite material sample 2 is captured by the infrared camera 4; Step 2, performing a laser impact test: the tiltable flat-nose pliers 1 clamp and fix the ceramic matrix composite material sample 2, the high-energy laser assembly aims at the middle position of the front side of the ceramic matrix composite material sample 2 to emit a high-energy laser, the high-speed camera 3 photographs the coating falling off and fiber ablation on the surface of the ceramic matrix composite material sample 2, and the infrared camera 4 photographs the thermal distribution cloud map of the front, back and side of the ceramic matrix composite material sample 2; Step 3: Analyze the test results: draw the "ablation depth-optical power" and "ablation radius-optical power" test curves and obtain the corresponding optical power values at the inflection points of the curves respectively. and , using an electronic universal testing machine to measure the residual tensile properties of the ceramic matrix composite material sample 2, characterizing the damage tolerance by the residual tensile strength, drawing a "residual tensile strength-optical power" curve, and obtaining the optical power value corresponding to the inflection point of the curve ; Step 4, perform finite element simulation on the laser impact test: establish a model of the ceramic matrix composite material in COMSOL software, set the parameters of the ceramic matrix composite material and the laser ablation related parameters and formulas to simulate the process of laser ablation of the ceramic matrix composite material; compare the ablation radius and ablation depth of the ceramic matrix composite material under different ablation times and light powers, draw the "ablation depth-light power" and "ablation radius-light power" simulation curves and obtain the light power values corresponding to the inflection points of the curves respectively. and ; Step 5: Comparison test results , and the simulated , By adjusting the simulation parameters in the COMSOL software, the experimental results are consistent with the simulation results, forming a simulation method that can accurately predict the anti-ablation performance of ceramic matrix composites.
[0024] As a preferred embodiment of the present invention, it may also have the following additional technical features: In this embodiment, the high-energy laser assembly includes a high-energy laser 5, a freely rotating gimbal 6, a low-energy laser aimer 7, and a water-cooled radiator 8. The high-energy laser 5 is used to emit a high-energy laser, the freely rotating gimbal 6 is used to drive the high-energy laser 5 to rotate to adjust the emission direction, the low-energy laser aimer 7 is used to emit an aiming laser, and the water-cooled radiator 8 is used to dissipate heat for the high-energy laser 5.
[0025] In this embodiment, three infrared cameras 4 are provided, and the three infrared cameras 4 respectively shoot the front side, the back side and the side of the ceramic-based composite material sample 2 .
[0026] In this embodiment, in step 3, the microscopic morphology of the ablated area of the ceramic matrix composite material sample 2 is observed under an optical microscope, and the degree of ablation of different components under different working conditions is compared.
[0027] In this embodiment, in step 3, and In The one with the closer value; if and If the ablation depth is closer, the ablation depth is used as the parameter to characterize the tensile damage tolerance of ceramic matrix composites; and To be closer, the ablation radius is used as a characterization parameter for the tensile damage tolerance of ceramic matrix composites.
[0028] Furthermore, in step 4, the laser ablation related formula specifically includes: Assuming that the distribution of charged particles is isotropic, and considering only the spatial variation in the thickness direction of the material, we take the thickness direction as x coordinates, the microscopic state of electrons and ions can be expressed by the distribution function , Description, satisfying the following Vlasov equations: ; ; in, is the electron charge, is the electron mass, is the self-consistent electric field strength, is the ion mass, is the ionic charge, is the ionic charge number, is the average number density of free electrons, is the average ion number density, is the speed of light, , are the source terms for producing free electrons and ions respectively; It's time. It’s speed; For femtosecond lasers, free electrons and ions are generated by two mechanisms: multiphoton ionization and avalanche ionization, namely: ; Among them, the subscript or ; is the multiphoton ionization rate, calculated by the Keldysh formula; ; in, is the laser power; , are complete elliptic integrals of the first and second kind, respectively; is the Keldysh parameter of the solid, expressed as: ; Parameters and Parameters according to The parameters are calculated: ; ; in, is the reduced Planck constant, is the band gap energy of the material, is the reduced mass of electrons and holes, is the hole mass; ; in, yes The integer part of: ; is the Dawson integral: ; is the photon ionization distribution, which is an arbitrary normalized function; ; is the avalanche ionization rate: ; in, is the avalanche ionization coefficient, It's electric current.
[0029] Reference Figure 2As shown, the present invention also provides a laser ablation damage tolerance test device for ceramic matrix composite materials, comprising a tiltable flat-nose pliers 1, a ceramic matrix composite material sample 2, a high-energy laser 5 assembly, a high-speed camera 3, and a plurality of infrared cameras 4, wherein the tiltable flat-nose pliers 1 clamp the ceramic matrix composite material sample 2, the high-energy laser 5 assembly is arranged in front of the ceramic matrix composite material sample 2 to emit high-energy laser toward the front of the ceramic matrix composite material sample 2, the high-speed camera 3 is arranged in front of the ceramic matrix composite material sample 2 to shoot toward the front of the ceramic matrix composite material sample 2, and the infrared camera 4 shoots toward the ceramic matrix composite material sample 2.
[0030] In this embodiment, the high-energy laser 5 component includes a high-energy laser 5, a free-rotating gimbal 6, a low-energy laser aimer 7, and a water-cooled radiator 8. The high-energy laser 5 and the low-energy laser aimer 7 are arranged on the free-rotating gimbal 6. The high-energy laser 5 is used to emit a high-energy laser. The free-rotating gimbal 6 is used to drive the high-energy laser 5 to rotate to adjust the emission direction. The low-energy laser aimer 7 is used to emit an aiming laser, and the aiming laser is parallel to and close to the high-energy laser. The water-cooled radiator 8 is arranged on the high-energy laser 5 to dissipate heat for the high-energy laser 5.
[0031] In this embodiment, three infrared cameras 4 are provided, and the three infrared cameras 4 are respectively provided in front of, behind and on one side of the ceramic-based composite material sample 2 .
[0032] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and improved concepts of the present invention within the technical scope disclosed by the present invention, and they should be covered by the protection scope of the present invention.
Claims
1. A laser ablation damage tolerance test method for ceramic matrix composite materials, characterized in that: The following steps are involved: Step 1, preparing a test device: the test device comprises a tiltable flat-nose pliers, a ceramic matrix composite material sample, a high-energy laser assembly, a high-speed camera, and a plurality of infrared cameras; the ceramic matrix composite material sample is clamped by the tiltable flat-nose pliers, a high-energy laser assembly is used to emit a high-energy laser to the ceramic matrix composite material sample, an image of the test process is captured by the high-speed camera, and a thermal distribution cloud map of the ceramic matrix composite material sample is captured by the infrared camera; Step 2, performing a laser impact test: the tiltable flat-nose pliers clamp and fix the ceramic matrix composite material sample, the high-energy laser assembly aims at the middle position of the front side of the ceramic matrix composite material sample to emit a high-energy laser, the high-speed camera photographs the coating falling off and fiber ablation on the surface of the ceramic matrix composite material sample, and the infrared camera photographs the thermal distribution cloud map of the front, back and side of the ceramic matrix composite material sample; Step 3, analyze the test results: draw the "ablation depth-optical power" and "ablation radius-optical power" test curves and obtain the corresponding optical power values at the inflection points of the curves respectively and The residual tensile properties of the ceramic matrix composite material sample were measured using an electronic universal testing machine, the damage tolerance was characterized by the residual tensile strength, a "residual tensile strength-optical power" curve was drawn, and the optical power value corresponding to the inflection point of the curve was obtained. ; Step 4, perform finite element simulation on the laser impact test: establish a model of the ceramic matrix composite material in COMSOL software, set the parameters of the ceramic matrix composite material and the laser ablation related parameters and formulas to simulate the laser ablation process of the ceramic matrix composite material; compare the ablation radius and ablation depth of the ceramic matrix composite material under different ablation times and light powers, draw the "ablation depth-light power" and "ablation radius-light power" simulation curves and obtain the light power values corresponding to the inflection points of the curves respectively. and ; Step 5: Comparative test results , and the simulated , By adjusting the simulation parameters in the COMSOL software, the experimental results are consistent with the simulation results, forming a simulation method that can accurately predict the anti-ablation performance of ceramic matrix composites.
2. The laser ablation damage tolerance test method for ceramic matrix composite materials according to claim 1, characterized in that: The high-energy laser assembly includes a high-energy laser, a freely rotating gimbal, a low-energy laser sight, and a water-cooled radiator. The high-energy laser is used to emit a high-energy laser, the freely rotating gimbal is used to drive the high-energy laser to rotate to adjust the emission direction, the low-energy laser sight is used to emit an aiming laser, and the water-cooled radiator is used to dissipate heat from the high-energy laser.
3. The laser ablation damage tolerance test method for ceramic matrix composite materials according to claim 1, characterized in that: There are three infrared cameras, and the three infrared cameras respectively shoot toward the front side, the back side and the side of the ceramic-based composite material sample.
4. The laser ablation damage tolerance test method for ceramic matrix composite materials according to claim 1, characterized in that: In step 3, the microscopic morphology of the ablated region of the ceramic matrix composite material sample is observed under an optical microscope, and the degree of ablation of different components under different working conditions is compared.
5. The laser ablation damage tolerance test method for ceramic matrix composite materials according to claim 1, characterized in that: In step 3, and In The one with the closer value; if and If the ablation depth is closer, the ablation depth is used as the parameter to characterize the tensile damage tolerance of ceramic matrix composites; and To be closer, the ablation radius is used as a characterization parameter for the tensile damage tolerance of ceramic matrix composites.
6. The laser ablation damage tolerance test method for ceramic matrix composite materials according to claim 1, characterized in that: In step 4, the laser ablation related formula specifically includes: Assuming that the distribution of charged particles is isotropic, and considering only the spatial variation in the thickness direction of the material, we take the thickness direction as x coordinates, the microscopic state of electrons and ions can be expressed by the distribution function , Description, satisfying the following Vlasov equations: ; ; in, is the electron charge, is the electron mass, is the self-consistent electric field strength, is the ion mass, is the ionic charge, is the ionic charge number, is the average number density of free electrons, is the average ion number density, is the speed of light, , are the source terms for producing free electrons and ions respectively; It's time. It’s speed; For femtosecond lasers, free electrons and ions are generated by two mechanisms: multiphoton ionization and avalanche ionization, namely: ; Among them, the subscript or ; is the multiphoton ionization rate, calculated by the Keldysh formula; ; in, is the laser power; , are complete elliptic integrals of the first and second kind, respectively; is the Keldysh parameter of the solid, expressed as: ; Parameters and Parameters according to The parameters are calculated: ; ; in, is the reduced Planck constant, is the band gap energy of the material, is the reduced mass of electrons and holes, is the hole mass; ; in, yes The integer part of: ; is the Dawson integral: ; is the photon ionization distribution, which is an arbitrary normalized function; ; is the avalanche ionization rate: ; in, is the avalanche ionization coefficient, It's electric current.
7. A laser ablation damage tolerance test device for ceramic matrix composite materials, characterized in that: The invention comprises a tiltable flat-nose pliers, a ceramic matrix composite material sample, a high-energy laser assembly, a high-speed camera, and a plurality of infrared cameras. The tiltable flat-nose pliers clamp the ceramic matrix composite material sample. The high-energy laser assembly is arranged in front of the ceramic matrix composite material sample to emit a high-energy laser toward the front of the ceramic matrix composite material sample. The high-speed camera is arranged in front of the ceramic matrix composite material sample to shoot toward the front of the ceramic matrix composite material sample. The infrared camera shoots toward the ceramic matrix composite material sample.
8. The laser ablation damage tolerance test device for ceramic matrix composite materials according to claim 7, characterized in that: The high-energy laser assembly includes a high-energy laser, a freely rotating gimbal, a low-energy laser sight, and a water-cooled radiator. The high-energy laser and the low-energy laser sight are arranged on the freely rotating gimbal. The high-energy laser is used to emit a high-energy laser. The freely rotating gimbal is used to drive the high-energy laser to rotate to adjust the emission direction. The low-energy laser sight is used to emit an aiming laser, and the aiming laser is parallel to and close to the high-energy laser. The water-cooled radiator is arranged on the high-energy laser to dissipate heat from the high-energy laser.
9. The laser ablation damage tolerance test device for ceramic matrix composite materials according to claim 7, characterized in that: There are three infrared cameras, which are respectively arranged in front, at the back and at one side of the ceramic-based composite material sample.
Citation Information
Patent Citations
Aircraft model modification system based on modal test data
CN103593518A
Strong laser and supersonic wind tunnel combined damage effect testing system and method
CN105973563A
Dynamic ablation measurement apparatus and dynamic ablation measurement method for online applying of impact load
CN106950128A
In-situ observation method for laser-induced ultrahigh-temperature ablation under high-speed airflow
CN115825061A
Simulator design and optimization integration method for predicting material service performance
CN117150864A
Cited By
Multi-scale prediction method for oxidative ablation behavior of carbon / carbon porous heat-proof material
CN120636642A